PENGARUH KUALITAS PELAYANAN PETUGAS PAJAK, SANKSI PERPAJAKAN, DAN PEMAHAMAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM LUWU UTARA - Iloh Maitri Padma Dewi; Naniek Noviari (Jurnal Ekonomi dan Bisnis, 2025)
Taxation serves as the primary source of state revenue and plays a crucial role in financing national development. However, taxpayer compliance particularly among Micro, Small, and Medium Enterprises (MSMEs) remains a persistent challenge within Indonesia's tax system. This study aims to analyze the influence of tax officer service quality, tax sanctions, and tax knowledge on the tax compliance of MSME taxpayers. A quantitative approach with a survey method was employed in this research. Data were collected through questionnaires distributed to MSME taxpayers selected using random sampling techniques. The data were analyzed using multiple linear regression. The findings of this study are expected to contribute to enhancing taxpayer compliance through improved service quality, strict enforcement of tax sanctions, and increased tax knowledge.